Why are Neurospora crassa crosses that are homozygous for a large duplication barren? - Ashwin Bhat; Durgadas P. Kasbekar (Fungal Genetics Reports, 2004)
Crosses homozygous for the duplication Dp(AR17) are barren regardless of RIP. Sad-1, a semi-dominant suppressor of meiotic silencing, suppresses the barrenness of duplication-heterozygous but not of duplication-homozygous crosses. Could it be that in the context of the homozygous cross the sad-1+ allele is not detected as being unpaired, and consequently, Sad-1 fails to suppress meiotic silencing?